Prenatal Alcohol Exposure and Autism Spectrum Disorder in 39 Children and Adults: Examination of Behavioural and Cognitive Profiles. Issue 1 (2nd January 2021) - Temple, Valerie; Cook, Jocelynn L.; Unsworth, Kathy; Roberts, Nicole
ABSTRACT: Introduction: There is significant symptom overlap between fetal alcohol spectrum disorder (FASD), which results from prenatal alcohol exposure (PAE), and autism spectrum disorder (ASD). There is also limited research regarding the comorbidity of these disorders. Method: Thirty-nine individuals with ASD and PAE (ASD+PAE) aged 3 to 30 years were matched for age, sex, and IQ to 78 individuals with PAE-only and compared on demographics, comorbid conditions, and 9 domains of neurodevelopmental function. Results: The ASD+PAE group were significantly more likely to have deficits in motor and daily living skills. They also had a greater number of impaired neurodevelopmental domains overall. They were diagnosed with ADHD more often and reported more sensory sensitivities, self-regulation difficulties, and social skills deficits. Conclusions: Overall, the ASD+PAE group had a more complex and severe presentation of symptoms. The relationship between ASD, FASD, and PAE as well as the value of providing an ASD diagnosis in the context of PAE are discussed.